2016
DOI: 10.12688/f1000research.8548.1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of dietary milk miRNAs by adult humans: a validation study

Abstract: Breast milk is replete with nutritional content as well as nucleic acids including microRNAs (miRNAs). In a recent report, adult humans who drank bovine milk appeared to have increased circulating levels of miRNAs miR-29b-3p and miR-200c-3p. Since these miRNAs are homologous between human and cow, these results could be explained by xeno-miRNA influx, endogenous miRNA regulation, or both. More data were needed to validate the results and explore for additional milk-related alterations in circulating miRNAs. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 44 publications
1
63
2
Order By: Relevance
“…101,102 Finally, positive results from a milk intake study involving humans 103 could not be validated. 104 Exciting and new concepts in the microRNA oeuvre must be supported by rigorous data. When dealing with very low RNA concentrations, one must be on the outlook for laboratory contaminants, nonspecific amplification, sequencing bias, and effects of analysis pipelines, among others, that are more parsimonious explanations for the presence of foreign RNA than hypothetical uptake pathways.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%
“…101,102 Finally, positive results from a milk intake study involving humans 103 could not be validated. 104 Exciting and new concepts in the microRNA oeuvre must be supported by rigorous data. When dealing with very low RNA concentrations, one must be on the outlook for laboratory contaminants, nonspecific amplification, sequencing bias, and effects of analysis pipelines, among others, that are more parsimonious explanations for the presence of foreign RNA than hypothetical uptake pathways.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%
“…A number of groups have searched for plant xenomiRs in human body fluids but have been unable to find these sequences at any substantial level (Snow et al 2013;Witwer et al 2013). Similarly, other groups were unable to detect dietary xenomiRs when conducting controlled feeding studies in humans, mice, bees, and other insects (Dickinson et al 2013;Witwer et al 2013;Auerbach et al 2016). Further, one independent research group investigated the xenomiR composition of sRNA-seq data from amphioxus animals, generated by the team of the original Zhang et al (2012) publication.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have not succeeded to validate the hypothesis that milk miRNAs exert physiological regulatory functions after transferring to offspring [126][127][128][129]. For instance, Auerbach et al [129] observed that drinking bovine milk increased circulating levels of miRNAs (miR-29b-3p and miR-200c-3p) but found no evidence that they significantly altered miRNA signals after milk ingestion. These authors concluded that milk miRNAs likely serve as a source of nutrition but not as post-transcriptional regulators in recipients.…”
Section: Microrna Function In Milk Recipientsmentioning
confidence: 99%